Agricultura camponesa e agronegócio: território em disputa na comunidade Apucaraninha, Cândido de Abreu/PR - Jensen, Mauro Rogério (2021)
The present work presents a discussion that starts from the concepts of territory, peasant agriculture and agribusiness. The focus of the research is the Apucaraninha Community, located in the municipality of Cândido de Abreu, state of Paraná. This research aimed to understand the advancement of the agribusiness productive model over the peasant territories in the community. The methodology of the work is based on bibliographic review and field research. As he resides in the studied community, the researcher can contribute with observations from his experience, which allowed establishing dialogues between the theory and the studied reality. It was identified that in the community there is a significant advance of agricultural commodities over the peasant territories, resulting in the replacement of food crops, including beans, by soybean production.